Structural Racism and the Will to Act - Lopez Bunyasi, Tehama (Radical Teacher, 2018)
In only a few short years, Black Lives Matter has shaped mainstream discourse of racial inequality so as to emphasize the disparate ways our society tends to value certain lives and contributions over others. In this essay, I describe how today's Black liberation movement inspired me to revise a graduate course on race and conflict that directs students to think about how contemporary institutions and social practices determine the value of life at the color line. In the epilogue, I ponder another round of revisions given the outcome of the 2016 presidential election.